The Influence of Brand Activation and Brand Image Using Tiktok @Kedas Beauty Pusat on Reseller Involvement in Kedas Beauty Products in South Sulawesi - Desi Ratnasari; Sudarnice Nays; Fitri Kumalasari (PT. Mawadaku Sukses Solusindo, 2024)
This research aims to determine: (1) The influence of brand activation using TikTok @Kedas Beautycentral on reseller involvement in Kedas Beauty products in South Sulawesi (2) The influence of brand image using TikTok @Kedas Beauty Pusat on reseller involvement in Kedas Beauty products in South Sulawesi. This research uses a quantitative method approach. Data collection in this research used literature studies, observations, interviews, distributing questionnaires via Google From. The population of this research is all resellers in South Sulawesi. Meanwhile, the sample for this study was 67 people. Research instrument testing uses validity and reliability tests with SPSS 2.0. The data analysis technique used in this research is measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 3.0. Based on the research results, it is known that there is a positive and significant influence between the brand activation variable on reseller involvement. This is proven by the original sample value of 0.365 and the t-statistic of 3.871 which is higher than the t-table value of 1.96 and brand image also has a positive and significant effect on reseller involvement because the original sample value is 0.596 and the t-statistic is 6.478 more. The size of the t-table value is 1.96. So the brand activation and brand image variables have a positive and significant effect on reseller involvement of 84.2%.